Analysis of Needs with the PIECES Concept: How Urgency is the Involvement of Ethical Hackers in Accounting Information Systems? - Yayang Novealita Wahono Putri; Kurnia Ekasari; Kartika Dewi Sri Susilowati (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to identify the needs analysis of a company in involving ethical hackers to achieve the desired goals. This research focuses on accounting information systems which are vital systems in business processes. The company's goals will be translated into a need analysis using the PIECES framework (Performance, Information, Economy, Control, Efficiency, and Service). The research method used is a quantitative descriptive method and uses documentation techniques in collecting data. This study uses secondary data in the form of a literature review of 80 journal articles published in 2018-2023. Only ISSN indexed journals are used as data sources to ensure the quality of research output remains relevant. The results of this study are that the information aspect holds the highest urgency at 31.25% and the control aspect ranks second with a score of 25.00%. While the aspect with the lowest urgency is the economic aspect with an achievement of only 6.25%. Comparison of the scope of research and how researchers explore in more detail in linking opportunity costs can be input for further research. Furthermore, future research can also link several concepts such as urgency needs analysis with the PIECES framework, opportunity costs, and user trust in ethical hackers. So that the results of the research conducted will be more interesting and can be a reference for companies in making policies.